Probing Iranian English Teachers' Communicative Activities and Perspectives on Iran’s Fundamental Reform Document of Education - Pourhosein Gilakjani, Abbas; Alizadeh, Mitra; Khazaee, Hossein; Sheikhy Behdani, Reihaneh (Register Journal, 2025)
In 2011, Iran’s educational system underwent a significant transformation through the implementation the Fundamental Reform Document of Education (FRDE). Alongside other revisions, the FRDE mandated reforms in English teaching practices to align with the communicative language teaching (CLT) principles. This study aims to (1) assess the communicativeness of English teaching practices in Iranian high schools using Littlewood’s (2004) continuum, (2) explore the perspectives of teachers regarding the FRDE and CLT, and (3) identify challenges in implementing the FRDE in English education. Data collection involved observing 60 English teaching sessions conducted by 15 English teachers from the first and second three years of high school. Subsequently, focus group interviews were conducted with the same teachers. The data were coded and analyzed using MAXQDA Analytics Pro 2020 and NVIVO 11. The results showed that most teaching activities used categorized by Littlewood’s (2004) as non-communicative and pre-communicative such as mechanical repetition, ask-and-answer practices, memorization and acting out conversations‎, ‎etc.‎ Notably, there was a limited representation of real-life communicative activities or structured communication tasks, indicating a systemic misalignment with CLT goals. The interviews provided insights into the varying opinions held by the teachers regarding the FRDE and CLT. While some teachers emphasized the values, others expressed concerns about its practicality in the Iranian context due to various constraints. These included the shortcomings of the FRDE, the unfamiliarity of the Iranian teachers with the CLT principles, the emphasis on teaching to the test, and the reluctance of students and parents to engage in practices beyond those preparing them for Iran’s university entrance exam (Konkur).